2007
DOI: 10.1300/j081v21n01_04
|View full text |Cite
|
Sign up to set email alerts
|

Housing and Connection to Nature for People with Dementia

Abstract: This paper reports on the qualitative findings of the first phase of the INDEPENDENT Project, an EPSRC funded EQUAL 4 consortium project in the UK that aims to investigate enabling environments for people with dementia. The overall project focus is on wellbeing and quality of life for people in different types of housing, with particular focus on the possible roles technology can play in maintaining the person's independence as long as possible. Connection to nature, access to the outdoors, and participation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 26 publications
2
70
0
2
Order By: Relevance
“…Access to areas, for example a toilet in each level, was perceived as very helpful to minimise night wandering (and thus reduce risk of falls and incontinence accidents). Previous research has also indicated that windows and adequate lighting are important for people with dementia to enhance safety and wellbeing (Torrington & Tregenza, 2007;Wong et al, 2014), to provide time and season orientation (van Hoof & Kort, 2009) and contributing to the feeling of them less isolated or trapped (De Witt, Ploeg, & Black, 2009;Gibson, Chalfont, Clarke, Torrington, & Sixsmith, 2007), but our findings highlighted the presence of big windows, pleasing views and brightness as important aspects also for carers. This of course depends on the surroundings outside, which in densely populated areas, may be problematic due to noise and the feeling of exposure.…”
Section: Discussionmentioning
confidence: 47%
“…Access to areas, for example a toilet in each level, was perceived as very helpful to minimise night wandering (and thus reduce risk of falls and incontinence accidents). Previous research has also indicated that windows and adequate lighting are important for people with dementia to enhance safety and wellbeing (Torrington & Tregenza, 2007;Wong et al, 2014), to provide time and season orientation (van Hoof & Kort, 2009) and contributing to the feeling of them less isolated or trapped (De Witt, Ploeg, & Black, 2009;Gibson, Chalfont, Clarke, Torrington, & Sixsmith, 2007), but our findings highlighted the presence of big windows, pleasing views and brightness as important aspects also for carers. This of course depends on the surroundings outside, which in densely populated areas, may be problematic due to noise and the feeling of exposure.…”
Section: Discussionmentioning
confidence: 47%
“…33,66 These losses are often associated with greater disablement in dementia. 67 Gibson and colleagues 5 have also reported that housing has impacted on well-being and quality of life for people with dementia through its connection to nature and access to the outdoors, which include opportunities for sensory stimulation and social interaction.…”
Section: Built Environmentmentioning
confidence: 99%
“…4 Moreover, a positive environment helps to mitigate cognitive impairment and interacting with nature supports people with multi-sensory stimulation, which positively affects people's mental, emotional and spiritual well-being. 5 In addition, the built environment is associated with physical activity, especially in promoting walking patterns amongst older adults. 6 These observations are important as recent prevalence profiles in the United Kingdom (UK) have suggested that there are 750,000 people with dementia living with the condition, of whom two-thirds live at home with the support of carers and/or other support networks, such as relatives, friends and neighbours.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Gardens in care homes can give older people the opportunity to engage in activities which enhance their wellbeing, such as gardening, watching birds or animals, and walking. 13 Although 17% of deaths in England occur in care homes, they are not specifically designed for the care of those who are at the end of life, and there may be practical difficulties in caring for relatively active residents in the same environment as those who are in the process of dying. 14,15 Hospices only provide care for a relatively small number of people, and they are the place of death for only 4% of people in England.…”
Section: Introductionmentioning
confidence: 99%